Comparative life table of Aphis pomi (Hemiptera: Aphididae) on two host plants Malus pumila L. and Chaenomeles japonica under laboratory conditions - Khadijeh Madahi; Ahad Sahragard (Journal of Crop Protection, 2012)
Life table parameters of Aphis pomi DeGeer (Hemiptera: Aphididae) were determined on two host plants: apple (Malus pumila L.) and flowering quince (Chaenomeles japonica Lindl.). This study was carried out under laboratory conditions (25 ± 1 ºC and RH of 70 ± 5 % and a photoperiod of 16: 8 h (L: D). The survivorship from first instar nymphs to adult was very close in M. pumila and C. japonica. The longevity of A. pomi was 8.1 ± 0.458 and 9.65 ± 0.412 days and the fecundity of female was 37.25 ± 2.198 and 32.9 ± 1.802 nymphs on M. pumila and C. japonica, respectively. Peaks of reproductive value occurred at ages of 8 and 9 days when reared on M. pumila and C. japonica, respectively. The intrinsic rate of increase (r) on M. pumila was higher than that on C. japonica, as it was 0.396 ± 0.015 on M. pumila and 0.329 ± 0.006 day-1 on C. japonica. The mean generation time (T) was 9.13 ± 0.35 and 10.62 ± 0.18 days, on M. pumila and C. japonica, respectively. The results showed that the two closely related host plants had significant influence on life table parameters of A. pomi and the aphid showed a better performance on M. pumila than on C. japonica. These results indicated that M. pumila is more suitable for A. pomi, resulting in a higher reproductive performance.